Українська підляська говірка в поезії Марії Сарнацької - Яворський, Андрій Юрійович; Yavorskyi, Andrii Yu. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У творах поетеси з Південного Підляшшя (Польща) Марії Сарнацької проаналізовано особливості місцевої української говірки, зокрема прокоментовано специфіку рефлексації давніх голосних, відмінності у вживанні приголосних, простежено специфіку формотворення іменників, прикметників, дієслів, відмінності у структурі та відмінюванні займенників. З’ясовано специфіку використання авторкою діалектних елементів. Peculiarities of Podlasie dialects, including specificity of long vowels relaxation, differences in the frequency of certain consonants usage, specificity of nouns, adjectives and verbs form-building, differences in pronoun structure and conjugation are fully and systematically reflected in the works of Ukrainian poet from the South Podlasie (Poland) Maria Sarnatska. Effects of different levels phenomena allowed to qualify the dialect used in the texts as an North Ukrainian. M. Sarnatska not only attempted to use certain dialect elements or imitation of dialect speech. Her works are written in Podlasie dialect, which essentially serves as a literary language. The texts fully represent the South Podlasie Ukrainian dialects and can be successfully used as a material for dialectological studies.
Ukrainian Podlasie dialect in Maria Sarnatska’s poetry
Keywords: підляські говірки; голосні фонеми; приголосні фонеми; словозміна; архаїзм; інновація; граматична аналогія; Podlasie dialects; vowel phonemes; consonant phonemes; inflections; archaism; innovation; grammatical analogy